Angles on a kingdom : East Anglian identities from Bede to Ælfric - Grossi, Joseph L., 1968- (Toronto ; Buffalo ; London : University of Toronto Press, 2021)
"From the eighth century to the turn of the millennium, East Anglia had a variety of identities thrust upon it by authors of the period who envisioned a unified England. Although they were not regional writers in the modern sense, Bede, Felix, the annalists of the Anglo-Saxon Chronicle, King Alfred of Wessex, Abbo of Fleury, and Ælfric of Eynsham took a keen interest in East Anglia, especially in its potential to undo English cultural cohesiveness as they imagined it. Angles on a Kingdom argues that those authors treated East Anglia as both a hindrance and a stimulus to the development of early English "national" consciousness. Combining close textual reading with consideration of early medieval barrow burials, coinage, border delineation, and rivalries between monastic houses, Joseph Grossi examines various forms of cultural affirmation and manipulation. Angles on a Kingdom shows that, over the course of roughly two and a half centuries, the literary metamorphoses of East Anglia hint at the region's recurring tensions with its neighbours--tensions which suggest that writers who sought to depict a coherent England downplayed what they deemed to be dangerous impulses emanating from the island's easternmost corner."--
Rædwald's unhappy realm : Bede's mixed views of East Anglian Imperium -- Æthelthryth in a virgin wilderness -- Solace for a client-king : Felix's Vita sancti Guthlaci -- Made in Wessex : Danish East Anglia and the Alfredian court -- Edmund, East Anglia, and England.
Includes bibliographical references and index.
Joseph Grossi is an associate professor in the Department of English and the Department of Hispanic and Italian Studies at the University of Victoria.
Print version record.
JSTOR
Keywords: English literature -- Old English, ca. 450-1100 -- History and criticism; East Anglia (England) -- In literature; Littérature anglaise -- ca 450-1100 (Vieil anglais) -- Histoire et critique; Est-Anglie (Angleterre) -- Dans la littérature.; LITERARY CRITICISM / Medieval; English literature -- Old English; Literature; England -- East Anglia; Kirchengeschichte; 450-1100; Literary criticism; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.